Pengembangan Media Pembelajaran Matematika Berbasis Website Dengan Pendekatan Kontekstual - Baihaqi, Rizal Baihaqi; Wulantina, Endah (Pendidikan Matematika Universitas PGRI Yogyakarta, 2023)
This study aims to develop a website-based learning media with a valid and interesting contextual approach. The research method used is Research And Development (R&D) with a 4D development model which includes 4 stages, namely define, design, development and disseminate. The location of this research is at MTs Ma'arif 23 Sendang Agung. The subjects in this study were class VIII students at MTs Ma'arif 23 Sendang Agung, totaling 24 students. The material developed is a flat sided space build material. The results of this study indicate that the product developed based on the validation of media experts obtains a percentage of 68% with the